ANALYSIS OF POVERTY DETERMINANTS IN REGENCIES/CITY OF BALI PROVINCE - Komang Rizky Ramadiputra; Made Dwi Setyadhi Mustika (Adisam Publisher, 2025)
Poverty is a complex issue influenced by economic and social factors, affecting individuals' ability to fulfill basic needs, participate in society, and maintain health. This study analyzes the impact of consumption, education, health, and population growth on poverty in Bali Province. The research comprises 72 observations from eight regencies and one city over the period 2016–2023. Data is collected through non- behavioral observation methods, including the review of books, articles, journals, and official documents from institutions such as the Central Bureau of Statistics. Quantitative analysis is employed to process the data. The findings reveal that consumption and education have a negative and significant effect on poverty, indicating that higher consumption and better education levels contribute to poverty reduction. Conversely, health has a positive and significant effect, suggesting that increased health indicators correlate with higher poverty levels. Meanwhile, population growth negatively influences poverty but lacks statistical significance. These findings underscore the importance of policies that promote local product empowerment, expand access to education, address the needs of the elderly, and ensure equitable income distribution. Such measures are essential to enhancing economic stability and mitigating the factors that contribute to poverty.